Error Analysis in Using Passive Voice among University Students: Comparative Taxonomy - Fadlia Azahra; Nur Sehang Thamrin; Afrillia Anggreni; Rofiqoh Rofiqoh (Journal of Pragmatics Research, 2026)
Passive voice remains a key grammatical structure for English learners, particularly in academic writing, yet many students struggle to use it accurately. This study analyzes the types of passive voice errors made by 19 fifth-semester students in the English Education Study Program at Tadulako University. Specifically, it addresses two questions: (1) How do classroom interaction patterns such as teacher-centered grammar instruction, limited student negotiation of meaning, or feedback practices shape students’ understanding and use of passive voice, and to what extent might these dynamics contribute to the dominance of developmental errors? (2) In what ways do students’ sociocultural backgrounds, prior educational experiences, and exposure to English outside the classroom influence their difficulties with auxiliary verbs and tense agreement, and how do these factors mediate tensions between Indonesian linguistic norms and English academic writing conventions? A quantitative design was employed, with a test focusing on passive constructions in present continuous, past continuous, and past perfect tenses. Students’ responses were categorized using Dulay et al.'s (1982) comparative taxonomy of developmental and interlingual errors. Results revealed developmental errors as the most prevalent (89.9%), mainly involving incorrect auxiliary verbs (is, am, are, being, been), past participle formation, and tense agreement. These findings highlight the need for targeted grammar instruction on auxiliary patterns and participles, alongside enhanced practice, corrective feedback, and adjustments to classroom interactions and sociocultural considerations to boost accuracy.